2021 Infusion Therapy Standards of Practice Updates. Issue 4 (July 2021) - Unknown
Abstract : EDITOR'S NOTE: INS strives to align the Standards with guidelines and clinical practice recommendations based on the most current evidence available. In our effort to provide consistent information and minimize confusion, this article outlines 4 corrections that will supersede recommendations published in January 2021. Please take a moment to carefully read through each item and make the appropriate updates to your clinical practice.